Modulation of Auditory Spatial Attention by Angry Prosody: An fMRI Auditory Dot-Probe Study - Ceravolo, Leonardo; Frühholz, Sascha; Grandjean, Didier (Frontiers in Neuroscience, 2016)
Emotional stimuli have been shown to modulate attentional orienting through signals sent by subcortical brain regions that modulate visual perception at early stages of processing. Fewer studies, however, have investigated a similar effect of emotional stimuli on attentional orienting in the auditory domain together with an investigation of brain regions underlying such attentional modulation, which is the general aim of the present study. Therefore, we used an original auditory dot-probe paradigm involving simultaneously presented neutral and angry non-speech vocal utterances lateralized to either the left or the right auditory space, immediately followed by a short and lateralized single sine wave tone presented in the same (valid trial) or in the opposite space as the preceding angry voice (invalid trial). Behavioral results showed an expected facilitation effect for target detection during valid trials while functional data showed greater activation in the middle and posterior superior temporal sulci (STS) and in the medial frontal cortex for valid versus invalid trials. The use of reaction time facilitation (absolute value of the Zscore of valid-(invalid+neutral)) as a group covariate extended enhanced activity in the amygdalae, auditory thalamus, and visual cortex. Taken together, our results suggest the involvement of a large and distributed network of regions among which the STS, thalamus, and amygdala are crucial for the decoding of angry prosody, as well as for orienting and maintaining attention within an auditory space that was previously primed by a vocal emotional event.